2013
DOI: 10.1007/s00520-013-1861-0
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment weight status and weight loss among head and neck cancer patients receiving definitive concurrent chemoradiation therapy: implications for nutrition integrated treatment pathways

Abstract: Purpose The purpose was to examine the effect of pretreatment weight status on loco-regional progression for patients with squamous cell carcinoma of the head and neck (SCCHN) after receiving definitive concurrent chemoradiation therapy (CCRT). Methods In an expanded cohort of 140 patients, we retrospectively reviewed weight status and loco-regional progression of SCCHN patients treated with CCRT between 2004 and 2010. Results Pretreatment ideal body weight percentage (IBW%) was statistically significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 43 publications
(48 reference statements)
2
9
0
Order By: Relevance
“…Subjects treated with MuGard were better able to maintain baseline weights than controls. Consistent with prior studies mean weight loss in the SC cohort was 9.14%. In contrast, mean weight loss in the MuGard cohort was 5.28%.…”
Section: Discussionsupporting
confidence: 89%
“…Subjects treated with MuGard were better able to maintain baseline weights than controls. Consistent with prior studies mean weight loss in the SC cohort was 9.14%. In contrast, mean weight loss in the MuGard cohort was 5.28%.…”
Section: Discussionsupporting
confidence: 89%
“…28,32 Head and neck cancers often have moderate to severe MN. [33][34][35][36] Findings here support these observations. Weight loss was common and severe; 72% of those assessed for UWL had either moderate or severe WL.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with head and neck squamous cell carcinoma (HNSCC) often experience unintentional weight loss during concomitant chemoradiotherapy (CCRT) . Studies have shown that up to 72% of this treatment‐related loss of body weight is due to loss of lean body mass (LBM) .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with head and neck squamous cell carcinoma (HNSCC) often experience unintentional weight loss during concomitant chemoradiotherapy (CCRT). [1][2][3] Studies have shown that up to 72% of this treatmentrelated loss of body weight is due to loss of lean body mass (LBM). 1,4 which again is associated with decline of functional performance, 4 quality of life (QoL), 5 as well as increased morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%